Pendekatan Sufistik dalam Pendidikan Adab perspektif KH. Jamaluddin Ahmad - Mukhammad Wahyudi (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2022)
Adab education is absolutely for anyone, anywhere and anytime because adab education is a tool to open students' doors of amaliah in reflecting on the elements of their faith. The purpose of this research is to analyze the adab education from the perspective of KH. Jamaluddin Ahmad holistically and practically in the educational process. This research is a literature study with the stages of data collection, reading, recording, reducing which are then processed to draw conclusions. The research results show that, according to KH. Jamaluddin Ahmad, adab education requires a sufistic approach both scientifically and practice in macro and micro scope, with the aim of students having a concrete landscape portrait of how to become a civilized student. The practical implementation of a sufistic approach can use the stimulus of previous Sufi tales or Sunni scholars, provided that the elements of Sufism in the saga refer to elements of adab practice in everyday life so that it becomes a guide in ethics. However, KH. Jamaluddin Ahmad continues to place the teacher as a central figure in adab education.